my textbook shows the result of n!/(n!+1) to be Does anyone know how they arrive at this result? Even wolfram shows something different. also latex is throwing errors whenever i use factorials.
Follow Math Help Forum on Facebook and Google+
It's actually n!/(n + 1)! = 1/(n + 1). This is because (n + 1)! = (n + 1)n!.
Thanks. why is it equal to that? is this a rule for distributing factorials over parentheses? i have not seen that rule before.
It's because N! = N(N - 1)(N - 2)...(3)(2)(1) = N(N - 1)!. What happens if N = n+1?
should be N!= n+1(n)(n-1)(n-2)...(4)(3)(2)(1)=N+1(N)!
First of all, you MUST use brackets where they are necessary and second, N and n are different. It should be N! = (n + 1)(n)(n - 1)...(3)(2)(1) = (n + 1)n!. Therefore (n + 1)! = (n + 1)n!
Originally Posted by skyd171 Thanks. why is it equal to that? is this a rule for distributing factorials over parentheses? i have not seen that rule before. What you posted, , is not true if . It is true that
Originally Posted by Plato What you posted, , is not true if . It is true that my math textbook is absurd, it does not mention that this relation is only true in a single scenario.
Originally Posted by skyd171 my math textbook is absurd, it does not mention that this relation is only true in a single scenario. I am not sure how to read that. But the is true:
View Tag Cloud